The Application of Quiz Team Technique to Improve Students’ Understanding on Simple Present Tense at Grade Seven at SMPN 26 Bandar Lampung - . Rosdawati (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
This research is based on students’ low participation and understanding on grammar especially in simple present tense by using Quiz Team Technique. It can make the learning process fun and not threatening. The quiz competition helps develop the students’ responsibility in mastering the materials individually or group. The purpose of this thesis is to find out the improvement of the students’ understanding by using Quiz Team Technique.Result of the study shows that the application of Quiz Team Technique in teaching simple present tense at SMPN 26 Bandar Lampung can be improved and get good responses. It can be seen that there is significant improvement from pre test to post test mean of experiment class (39.4 to 63.05). The other result using t-Test, t-value is greater than p-value. In the other words, 5.07 is greater than 2.71 and 2.02. The result indicated that there was a improvement of students’ understanding on Simple Present Tense by using Quiz Team Technique.